Pengaruh Persepsi Harga dan Kualitas Pelayanan Terhadap Minat Pembelian Pengguna RedDoorz Tasikmalaya - Nabila Annisa Fitri; Arga Sutrisna; Barin Barlian (Journal of Management and Social Sciences, 2023)
This study aims to identify and analyze the effect of price perceptions and service quality onpurchase intention (a survey of RedDoorz Tasikmalaya company users). The method used in this research is causality with a quantitative approach. With a research sample of 49 Users of the Tasikmalaya RedDoorz Company. The data used is using primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Price Perception has a very good rating classification, Service Quality has a very good rating classification while Purchase Intention has a Good classification for RedDoorz Tasikmalaya Company Users. Taken together, Perceived Price and Service Quality have a significant influence on Purchase Intention of Company Users of RedDoorz Tasikmalaya. Partially Perceived Price has a significant influence on Purchase Intention of Company Users of RedDoorz Tasikmalaya. Partially, Service Quality has a significant effect on Purchase Interest in RedDoorz Tasikmalaya Company Users.